Antimicrobial activity and bioguided fractionation of Rumex tingitanus extracts for meat preservation. (March 2017) - Mhalla, Dhekra; Bouaziz, Amira; Ennouri, Karim; Chawech, Rachid; Smaoui, Slim; Jarraya, Raoudha; Tounsi, Slim; Trigui, Mohamed
Abstract: This study was undertaken to investigate the antibacterial and antifungal activities of Rumex tingitanus leaves extracts as well as the identification of bioactive components and their performance in meat preservation. Total phenolics and flavonoids showed the highest content of phenolics and flavonoids in the ethyl acetate fraction (Rt EtOAcF). For antimicrobial efficacy, leaves extract and derived fraction were tested for their capacity to inhibit bacterial and fungal proliferation in vitro and in vivo . The ethyl acetate fraction showed the most potent antibacterial and antifungal activities compared to the others extracts. Thus, the efficacy of this extract to inhibit the proliferation of Listeria monocytogenes in minced beef meat model was examined. This fraction eradicates the L. monocytogenes population in meat in a concentration- and time-dependent manner. A bio-guided purification of the Rt EtOAc fraction resulted in the isolation of the compound responsible for the observed antimicrobial activity. This compound was identified as luteolin by analysis of spectroscopic data. Chemical compounds isolated in this article: Luteolin (PubChem CID: 5280445); p -iodonitrotetrazolium chloride (PubChem CID: 64957); Amphotericin B (PubChem CID: 5280965); Gentamicin and (PubChem CID: 6419933); Hexane (PubChem CID: 8058); Methanol (PubChem CID: 887); Ethanol (PubChem CID: 702); Dimethylsulfoxide (PubChem CID: 679); Quercetin (PubChem CID: 5280343); Gallic acid (PubChem CID: 370).